2019
DOI: 10.3390/genes10120954
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Spontaneous Abortion in Holstein Heifers and Primiparous Cows

Abstract: Background: The objectives of this study were to identify loci, positional candidate genes, gene-sets, and pathways associated with spontaneous abortion (SA) in cattle and compare these results with previous human SA studies to determine if cattle are a good SA model for humans. Pregnancy was determined at gestation day 35 for Holstein heifers and cows. Genotypes from 43,984 SNPs of 499 pregnant heifers and 498 pregnant cows that calved at full term (FT) were compared to 62 heifers and 28 cows experiencing SA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 100 publications
(123 reference statements)
1
3
0
Order By: Relevance
“…The additive genomic variance observed in this study was greater than previously reported by others for abortion and/or embryo loss [ 23 , 35 , 36 ], which explained more than 12% of the variability in abortion incidence. The heritability estimates for abortion were similar to those reported in previous studies [ 22 , 23 , 35 , 37 ], although they were lower than the estimates reported by Bamber et al [ 38 ] and Sigdel et al [ 22 ] (multiparous cows only). Even though these studies, including this one, have used different approaches to evaluate genomic markers of abortion risk, the fact that heritability and additive genetic variance are greater than 0 supports the hypothesis that it is feasible to select toward reduced abortion risk based on genomic evaluations.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The additive genomic variance observed in this study was greater than previously reported by others for abortion and/or embryo loss [ 23 , 35 , 36 ], which explained more than 12% of the variability in abortion incidence. The heritability estimates for abortion were similar to those reported in previous studies [ 22 , 23 , 35 , 37 ], although they were lower than the estimates reported by Bamber et al [ 38 ] and Sigdel et al [ 22 ] (multiparous cows only). Even though these studies, including this one, have used different approaches to evaluate genomic markers of abortion risk, the fact that heritability and additive genetic variance are greater than 0 supports the hypothesis that it is feasible to select toward reduced abortion risk based on genomic evaluations.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, there was a positive genetic correlation between Z_Abort and Z_Calf Livability. Previous studies have suggested that markers for abortion are related to genes governing the development of the placenta and fetal immune system, among other functions [ 22 , 37 ]. Therefore, it is possible that cows with high risks of abortions will give birth to calves that have compromised in utero development and with a greater risk of early death or disease.…”
Section: Discussionmentioning
confidence: 99%
“…The enrichment scores were then normalized (NES) to account for the number of genes within the gene set. Enriched gene sets for HCR1 were defined as those with NES ≥ 3.0, which is comparable to previous fertility studies [ 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Non-infectious factors that cause abortion include metabolic disorders, hormonal disorders, trauma, heat stress, and nutritional deficiencies (Michael 1993). Foot-and-mouth viral infections (Ranjan et al 2016) and genetic disorders have also been reported to cause abortion (Oliver et al 2019).…”
Section: ■ Introductionmentioning
confidence: 99%